Fcγ receptor expression on splenic macrophages in adult immune thrombocytopenia. (28th February 2017) - Audia, S; Santegoets, K; Laarhoven, A G; Vidarsson, G; Facy, O; Ortega-Deballon, P; Samson, M; Janikashvili, N; Saas, P; Bonnotte, B; Radstake, T R
Summary: Splenic macrophages play a key role in immune thrombocytopenia (ITP) pathogenesis by clearing opsonized platelets. Fcγ receptors (FcγR) participate in this phenomenon, but their expression on splenic macrophages and their modulation by treatment have scarcely been studied in human ITP. We aimed to compare the phenotype and function of splenic macrophages between six controls and 24 ITP patients and between ITP patients according to the treatments they received prior to splenectomy. CD86, human leucocyte antigen D-related (HLA-DR) and FcγR expression were measured by flow cytometry on splenic macrophages. The major FcγR polymorphisms were determined and splenic macrophage function was assessed by a phagocytosis assay. The expression of the activation markers CD86 and HLA-DR was higher on splenic macrophages during ITP compared to controls. While the expression of FcγR was not different between ITP and controls, the phagocytic function of splenic macrophages was reduced in ITP patients treated with intravenous immunoglobulin (IVIg) within the 2 weeks prior to splenectomy. The FCGR3A (158V/F) polymorphism, known to increase the affinity of FcγRIII to IgG, was over-represented in ITP patients. Thus, these are the first results arguing for the fact that the therapeutic use of IVIg during human chronic ITP does not modulate FcγR expression on splenic macrophages but decreases their phagocytic capabilities. Graphical Abstract: